Determination of the absolute configuration of phosphinic analogues of glutamate. Issue 4 (24th November 2014) - Commare, Bruno; Rigault, Delphine; Lemasson, Isabelle A.; Deschamps, Patrick; Tomas, Alain; Roussel, Pascal; Brabet, Isabelle; Goudet, Cyril; Pin, Jean-Philippe; Leroux, Frédéric R.; Colobert, Françoise; Acher, Francine C.
Abstract : Stereomers ofLSP1-2111 have been separated, their absolute configuration and agonist activity at mGlu4R determined. Abstract : A series of phosphinic glutamate derivatives ( e.g. LSP1-2111 ) have been proven to be potent agonists of metabotropic glutamate (mGlu) receptors and shown promising in vivo activity. However, so far all were synthesized and tested as a mixture of two diastereomers whose absolute and relative configurations are not known. In this study, the stereomers were separated on a Crownpack CR(+) column and their absolute configuration was assessed by means of a diastereoselective synthesis. Both separatedl -stereomers activated the mGlu4 receptor with EC50 's of 0.72 and 4.4 μM for (1 S, 1′ S )-and (1 S, 1′ R )-LSP1-2111, respectively.